2015
DOI: 10.1155/2015/325657
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Reversible Encephalopathy Syndrome due to High Dose Corticosteroids for an MS Relapse

Abstract: Increased blood pressure is a known adverse effect associated with corticosteroids but little is published regarding the risk with the high doses used in multiple sclerosis (MS). A 53-year-old female with known relapsing remitting MS presented with a new brainstem relapse. Standard of care treatment for an acute MS relapse, 1250 mg of oral prednisone for 5 days, was initiated. She developed an occipital headache and dizziness and felt generally unwell. These symptoms persisted after treatment was complete. On … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 19 publications
2
9
0
Order By: Relevance
“…Our finding of frequent steroid exposure prior to PRES is consistent with numerous case reports demonstrating a temporal association between steroid exposure and PRES [5, 8, 12, 19, 20, 23, 24, 30, 31, 34, 38, 47, 48]. In our cohort and in the literature, steroid therapy is often co-administered with other potential culprit drugs or administered in the context of nephritis, which causes hypertension.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our finding of frequent steroid exposure prior to PRES is consistent with numerous case reports demonstrating a temporal association between steroid exposure and PRES [5, 8, 12, 19, 20, 23, 24, 30, 31, 34, 38, 47, 48]. In our cohort and in the literature, steroid therapy is often co-administered with other potential culprit drugs or administered in the context of nephritis, which causes hypertension.…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with reports of PRES occurring after isolated exposure to steroids in non-autoimmune disorders, such as in asthma and brain metastasis [20, 24]. Similarly, PRES has been reported in patients receiving steroid therapy for autoimmune conditions that do not cause nephritis, such as neuromyelitis optica and multiple sclerosis [30, 34]. Among patients with lupus, PRES has been described after high-dose steroids in the absence of nephritis [5].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…It has been suggested that CSA may contribute to PRES in HLH, 37,38 but PRES has also been associated with other drugs, including corticosteroids. 39,40 Notably, encephalopathy is common in the natural course of HLH, and CSA has been reported to be beneficial in rheuma-associated HLH/macrophage activation syndrome. 41 In our data, we found no evidence of a marked increase of CSA-induced PRES.…”
Section: Patients Alive Without Hsctmentioning
confidence: 99%
“…High-dose steroids, azathioprine, cyclophosphamide, asparaginase, and methotrexate have all been individually associated with PRES. [ 12 13 14 ] Some of our patients were on one or more of these medications when diagnosed with PRES. Since primary disease control is equally important, expert help is required to modulate the medications so as to control both, the disease and symptoms of PRES.…”
Section: Discussionmentioning
confidence: 99%